Appraising spatial inequalities in urban water access in African cities by means of GIS clustering: insights from Malabo, Equatorial Guinea - S. Meñe-Nsue-Mikue; V. Gómez-Escalonilla; E. Montero-González; S. Díaz-Alcaide; M. Rodríguez del Rosario; P. Martínez-Santos (Utilities Policy, 2026)

The evolution of the cave's entrance of Bruniquel and consequences for its accessibility by early Homo neanderthalensis - K. Génuite; S. Verheyden; H. Camus; C. Burlet; M. Boudadi-Maligne; L. Bruxelles; H. Cheng; D. Cochard; S. Delaby; E. Fabre; C. Ferrier; C. Lézin; et al. (Quaternary Science Reviews, 2026)

A non-invasive method to monitor farmland bird exposure to triazole fungicides - Elena Fernández-Vizcaíno; François Mougeot; Rafael Mateo; Pablo R. Camarero; Vicente Alcaide; Manuel E. Ortiz-Santaliestra (Chemosphere, 2023)

A comparison of genomic islands of differentiation across three young avian species pairs - Darren E. Irwin; Borja Milá; David P. L. Toews; Alan Brelsford; Haley L. Kenyon; Alison N. Porter; Christine Grossen; Kira E. Delmore; Miguel Alcaide; Jessica H. Irwin (Molecular Ecology, 2018)
Detailed evaluations of genomic variation between sister species often reveal distinct chromosomal regions of high relative differentiation (i.e., “islands of differentiation” in F ST ), but there is much debate regarding the causes of this pattern. We briefly review the prominent models of genomic islands of differentiation and compare patterns of genomic differentiation in three closely related pairs of New World warblers with the goal of evaluating support for the four models. Each pair (MacGillivray's/mourning warblers; Townsend's/black‐throated green warblers; and Audubon's/myrtle warblers) consists of forms that were likely separated in western and eastern North American refugia during cycles of Pleistocene glaciations and have now come into contact in western Canada, where each forms a narrow hybrid zone. We show strong differences between pairs in their patterns of genomic heterogeneity in F ST , suggesting differing selective forces and/or differing genomic responses to similar selective forces among the three pairs. Across most of the genome, levels of within‐group nucleotide diversity ( π Within ) are almost as large as levels of between‐group nucleotide distance ( π Between ) within each pair, suggesting recent common ancestry and/or gene flow. In two pairs, a pattern of the F ST peaks having low π Between suggests that selective sweeps spread between geographically differentiated groups, followed by local differentiation. This “sweep‐before‐differentiation” model is consistent with signatures of gene flow within the yellow‐rumped warbler species complex. These findings add to our growing understanding of speciation as a complex process that can involve phases of adaptive introgression among partially differentiated populations.

An outbreak of Shewanella putrefaciens group in wild eels Anguilla anguilla L. favoured by hypoxic aquatic environments - C Esteve; R Merchán; E Alcaide (Journal of Fish Diseases, 2017)
Microbiological analyses were conducted on wild eels from the L′Albufera Lake (Spain). A total of 174 individuals were collected in two surveys (i.e. year 2008 and autumn–winter 2014) among those caught by local fishermen into the lagoon. The prevalence of Shewanella putrefaciens group was 1.7% in 2008 and rose above 32% in 2014. It was due to an outbreak of shewanellosis that presented a morbidity rate of 64%. S. putrefaciens group strains were isolated as pure cultures from the sick eels that showed white ulcers surrounded by a reddish inflammation, damage of the mouth, extensive skin discoloration, exophthalmia, ascites and bad odour. The S. putrefaciens group was recovered from freshwater samples taken at the L′Albufera system, along autumn–winter 2015. Its counts significantly increased in freshwater parallel to hypoxia and temperature rising. Shewanellae strains were identified as S. putrefaciens and S. xiamenensis by 16S rRNA gene sequencing. These isolates recovered from sick eels or freshwater were virulent for European eel by IP challenge ( LD 50 10 6 CFU g −1 body weight). They also caused 30–38% cumulative mortality, in European eels challenged by a 2‐h bath (10 7 CFU mL −1 ). These results suggest that shewanellosis could be transmitted through water highlighting the fact that hypoxic conditions increase this bacterium levels in water.

Recurrent selection explains parallel evolution of genomic regions of high relative but low absolute differentiation in a ring species - Darren E. Irwin; Miguel Alcaide; Kira E. Delmore; Jessica H. Irwin; Gregory L. Owens (Molecular Ecology, 2016)
Recent technological developments allow investigation of the repeatability of evolution at the genomic level. Such investigation is particularly powerful when applied to a ring species, in which spatial variation represents changes during the evolution of two species from one. We examined genomic variation among three subspecies of the greenish warbler ring species, using genotypes at 13 013 950 nucleotide sites along a new greenish warbler consensus genome assembly. Genomic regions of low within‐group variation are remarkably consistent between the three populations. These regions show high relative differentiation but low absolute differentiation between populations. Comparisons with outgroup species show the locations of these peaks of relative differentiation are not well explained by phylogenetically conserved variation in recombination rates or selection. These patterns are consistent with a model in which selection in an ancestral form has reduced variation at some parts of the genome, and those same regions experience recurrent selection that subsequently reduces variation within each subspecies. The degree of heterogeneity in nucleotide diversity is greater than explained by models of background selection, but is consistent with selective sweeps. Given the evidence that greenish warblers have had both population differentiation for a long period of time and periods of gene flow between those populations, we propose that some genomic regions underwent selective sweeps over a broad geographic area followed by within‐population selection‐induced reductions in variation. An important implication of this ‘sweep‐before‐differentiation’ model is that genomic regions of high relative differentiation may have moved among populations more recently than other genomic regions.

Multidrug-resistant (MDR) Aeromonas recovered from the metropolitan area of Valencia (Spain): diseases spectrum and prevalence in the environment - C. Esteve; E. Alcaide; M. J. Giménez (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Presence of viruses in wild eels Anguilla anguilla L, from the Albufera Lake (Spain) - I Bandín; S Souto; J M Cutrín; C López‐Vázquez; J G Olveira; C Esteve; E Alcaide; C P Dopazo (Journal of Fish Diseases, 2014)
A virological analysis was conducted on wild eels from the Albufera Lake (Spain). A total of 179 individuals at different growth stages were collected in two different surveys (2004 and 2008). Presence of anguillid herpesvirus (Ang HV ‐1), aquabirnavirus and betanodavirus was confirmed by PCR procedures in both surveys, although the number of detections was clearly higher in 2008 (83% of the eels analysed resulted positive for virus presence). Ang HV ‐1 was the viral agent most frequently detected, followed by aquabirnaviruses. Betanodaviruses were detected by the first time in wild eels, and although the detections were only made by nested PCR , high percentage of positives were achieved. In addition, in 2008, seven aquabirnaviruses were isolated. Phylogenetic analysis performed using partial sequences of both genomic segments of aquabirnaviruses indicated that the seven isolates could be typed as WB (genogroup I) on the basis of segment A sequences, but when segment B was used six of them clustered with C1 strain (genogroup V) and one was typed as Ab (genogroup II). These results indicate natural reassortment between different strains of aquabirnaviruses in the eels. Although betanodaviruses were not isolated in cell culture, the analysis of the sequence of the nested PCR product indicated that they clustered with SJNNV genotype. The diversity of viral agents and the high level of viral detections suggest that viral infections may play a more prominent role in the decline of the European eel than initially thought.

Multilocus analysis of variation using a large empirical data set: phenylpropanoid pathway genes in Arabidopsis thaliana - S. E RAMOS‐ONSINS; E PUERMA; D BALAÑÁ‐ALCAIDE; D SALGUERO; M AGUADÉ (Molecular Ecology, 2008)
Detecting the signature of adaptation on nucleotide variation is often difficult in species that like Arabidopsis thaliana might have a complex demographic history. Recent re‐sequencing surveys in this species provided genome‐wide information that would mainly reflect its demographic history. We have used a large empirical data set (LED) as well as multilocus coalescent simulations to analyse sequence variation at loci involved in the phenylpropanoid pathway of this species. We surveyed and examined DNA sequence variation at nine of these loci (about 19.7 kb) in 23 accessions of A. thaliana and one accession of its closely related species Arabidopsis lyrata . Nucleotide variation was lower at nonsynonymous sites than at silent sites in all loci, indicating generalized functional constraint at the protein level. No association between variation and position in the metabolic pathway was detected. When the data were contrasted against the standard neutral model, significant deviations for silent variation were detected with Tajima's D , Fu's F S and Fay and Wu's H multilocus test statistics. These deviations were in the same direction than in previous large‐scale multilocus analyses, suggesting a genome‐wide effect. When the nine‐locus data set was contrasted against the large empirical data set, the level (Watterson's θ) and pattern of variation (Tajima's D ) detected in these loci did not deviate either at the single‐locus or multilocus level from the corresponding empirical distributions. These results would support an important role of the demographic history of A. thaliana in shaping nucleotide variation at the nine studied phenylpropanoid loci. The potential and limitations of the empirical distribution approach are discussed.

Highly structured nucleotide variation within and among Arabidopsis lyrata populations at the FAH1 and DFR gene regions - D. BALAÑÁ‐ALCAIDE; S. E. RAMOS‐ONSINS; Q. BOONE; M. AGUADÉ (Molecular Ecology, 2006)
Nucleotide variation at the FAH1 and DFR gene regions was surveyed in four populations of Arabidopsis lyrata (two European A. l. petraea and two North American A. l. lyrata populations). In contrast to previous results, levels of variation were not consistently lower in A. l. lyrata than in A. l. petraea , and similar degrees of genetic differentiation were detected between and within subspecies. These observations and the significant genetic differentiation detected among populations suggest population substructure and no real subdivision between subspecies. For each gene studied, genotypic data were obtained, which allowed comparing nucleotide diversity within individuals (between sequences from the same individual) and within populations (between sequences from the same population). The generally lower level of variation within than among individuals detected in each population yielded a significant deviation from panmixia within populations. In three of the four populations studied, two highly divergent alleles were detected within populations at the highly variable DFR locus. This pattern and the significant excess of derived variants detected in most populations suggest that most variation segregating within populations results from rare migration events between relatively small and isolated populations exhibiting reduced panmixia.

Vibrio harveyi causes disease in seahorse, Hippocampus sp. - E Alcaide; C Gil‐Sanz; E Sanjuán; D Esteve; C Amaro; L Silveira (Journal of Fish Diseases, 2001)